THE MEANING BEHIND THROWING CHICKEN IN WEDDING CEREMONY Study of Kudus Kulon AndWetan Society - Fadhlullah, Muhammad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2015)
Our living traditions are an inheritance from our ancestors. One of them is Chicken Throwing ritual in Kudus City. This tradition celebrated when a villager of Kudus Kulon get married with Kudus Wetan society or in contrary. A villager should throw a chicken in Gelis bridge to eliminate the bad effect from spirits in this bridge. Almost of old people in the past include meaning in every tradition, they give some message not directly but in symbols. So thatâ€™s way the author want to describe what the meaning behind chicken throwing in wedding ceremony of Kudus society. This research used a qualitative method trough in depthÂ interview to gain data. To analysis data, this research used the semiotic of Charles Sander Pierce. In sum, the tradition of Chicken Throwing has many meanings. Firstly, in Hindhu era this tradition was a symbol of offering that give to the spirits in Gelis river. Secondly in followers of Sunan Kudus era this tradition has the different meaning. They move to the purpose of this tradition became shodaqoh given to the vagrants. Thirdly, in this era it is carried out only on the basis of orders from parents or just hereditary